Characteristics and thermodynamics of the interaction of 6-shogaol with human serum albumin as studied by isothermal titration calorimetry - Shevin Rizal Feroz; Sri Nurestri Abdul Malek; Saad Tayyab
ABSTRACT The interaction between 6-shogaol, a pharmacologically active ginger constituent, and human serum albumin (HSA), the main in vivo drug transporter, was investigated using isothermal titration calorimetry (ITC). The value of the binding constant, Ka (5.02 ± 1.37 × 104 M−1) obtained for the 6-shogaol-HSA system suggested intermediate affinity. Analysis of the ITC data revealed feasibility of the binding reaction due to favorable enthalpy and entropy changes. The values of the thermodynamic parameters suggested involvement of van der Waals forces, hydrogen bonds and hydrophobic interactions in the 6-shogaol-HSA complex formation.